Diltiazem treatment for the management of ischaemia in patients with poor left ventricular function: safety of long term administration. Issue 5 (November 1987) - Zema, M J; Perlmutter, S; Mankes, S; Nikitopoulos, C
Abstract : The tendency of oral diltiazem (a calcium entry blocking agent and a negative inotrope) to induce or exacerbate congestive heart failure when used for the long term management of myocardial ischaemia in patients with poor left ventricular function has not been investigated before. Twenty two patients (aged 42-73 years) with pretreatment left ventricular ejection fraction ranging from 0.11 to 0.39 were given open label oral diltiazem (120-360 mg/24 h (mean 254 mg)) for two weeks to 16 months (mean 7.5 months, median 6.2 months). There was a weight change of greater than 3 lb (1.35 kg) in nine patients--five gained weight and four lost it. Diltiazem treatment did not alter the mean (SD) cardiothoracic ratio on chest x ray (0.47 (0.06) before vs 0.48 (0.05) after) or the left ventricular ejection fraction at rest (0.28 (0.09) before vs 0.26 (0.08) after). Diltiazem was discontinued in one patient because of symptoms indicative of worsening congestive heart failure. No patient required admission to hospital for treatment of symptoms resulting from further left ventricular decompensation. Diltiazem was discontinued in six other patients for other reasons. Long term administration of oral diltiazem was not regularly associated with a deterioration in clinical, radiographic, or radionuclide ventriculographic estimates of left ventricular function, even in patients with poor baseline left ventricular systolic performance.